Defining the meaning and scope of digital transformation in higher education institutions - Gkrimpizi, Thomais; Peristeras, Vassilios; Magnisalis, Ioannis (Administrative sciences, 2024)
Digital transformation has emerged as a pervasive force in today's rapidly evolving world, touching almost every sector and industry. In the higher education sector, in which education, research, and knowledge dissemination hold paramount significance for society, the notion of digital transformation per se becomes particularly important. This paper focuses specifically on higher education, acknowledging that it exists in a broader environment. In this work, qualitative methods were applied to explore the meaning and scope of digital transformation in higher education institutions. The systematic literature review formed the basis for in-depth interviews with experts in the discipline to explore the meaning and scope of digital transformation in higher education institutions. Then, for the purpose of preparing the case study, the concepts that emerged from the systematic literature review and interviews with experts were grouped together through a keyword-based pattern. Lastly, a case study was conducted at a Greek university with the aim of better understanding the way in which university members of a particular higher education institution perceive the meaning and scope of digital transformation. Our analysis provides valuable insights into higher education institutions for decision-makers and those involved in digital transformation initiatives, offering a comprehensive definition of digital transformation in higher education institutions. Finally, this paper can also serve as a basis for researchers who are interested in defining the meaning and scope of digital transformation in their own research fields.